Second-Person References in Netizens’ Comments on Lambe Turah’s New Instagram Post: Analysis and Implication - Budi Hermawan; R. Dian Dia-an Muniroh; Ni’matusy Syifa Auliya (Syntax Literate, 2023)
Social media, particularly Instagram, has become a popular platform for users to interact and share information. One account that has attracted attention is "Lambe Turah," which often shares news and other exciting content. This research analyzes the second persona references in the comments of netizens on the Instagram account of Lambe Turah. The findings indicate differences in perspectives, evaluation of actions, and discussions regarding behavior implications in a domestic violence case involving Rizky Billar and Lesti Kejora. Using the second persona references influences the interaction and communication among netizens, building relationships, shared understanding, and social influence. This article provides a deeper understanding of the dynamics of communication and the perspectives of netizens in social media.